Foot-and-mouth disease in Asia - Md. Abdur Rahman; Farah Zereen; Md. Liton Rana; Md. Golzar Hossain; Masaru Shimada; Sukumar Saha (Virus Research)
Foot-and-mouth disease (FMD) is a highly contagious transboundary disease prevalent across the Asian continent, affecting both wild and domestic artiodactyls. The disease is caused by a virus belonging to the Aphthovirus genus of the Picornaviridae family which is categorized into seven serotypes: C, O, A, SAT1, SAT2, SAT3, and Asia1. The virus spreads through direct and indirect contact, including semen, meat, fomites, ingestion, and aerosols. FMD has a severe economic impact due to the high morbidity and mortality, especially in young animals. Prevention of the disease relies on vaccination with the prevalent serotype(s) or the slaughter and destruction of affected animals. This review discusses the prevalence of various FMD virus (FMDV) serotypes across Asia, along with the transmission modes, pathogenesis, immune response, and immune suppression by FMDV. Additionally, the review explores FMD diagnosis, prevention, and control strategies, and highlights future opportunities for research aimed at developing strain-specific viral and bacterial combined vaccines.